Simulation of subnanosecond radio pulse electro-optical repeater - A. V. Shiltsin; M. S. Kostin (Российский технологический журнал)
Objectives. The study aimed to construct and analyze a computational model of an electro-optical repeater of radio pulses, capable of reconstructing a pulsed radio image with subnanosecond resolution in a single reception under conditions of additive noise.Methods. Numerical methods of network analysis were used, which are the basis of specialized computer-aided design systems, numerical methods of statistical radio engineering.Results. A radiophotonic radio pulse repeater scheme was constructed, which is implemented based on the principle of fractional multiplexing with delayed feedback. Software simulation of infrared repeaters in the Simulink environment (Trial Version Soft) was developed, which allows for analyzing and investigating the efficiency of the optical reconstruction method of radio pulses using a fractional multiplexing with delayed feedback. It is shown that repeaters schemes, implemented on the principles of fractional multiplexing with delayed feedback, are able to effectively solve the scientific and practical problems of multiple probing of objects with ultrashort pulses (USP) for obtaining a radio image of a target with reliable reproducibility. In the course of numerical simulations, it was found that the two- and four-cascade schemes of delay lines with feedback do not provide reliable reproducibility in the case of reconstruction of an ultrashort pulse with a complex time profile. At the same time, the scheme with a cascade of 8 delay lines showed good results, providing a correlation reproducibility of more than 0.9. In this case, the scheme of an electro-optical repeater with a cascade of 16 delay lines did not make a significant contribution to increasing the accuracy of the USP reconstruction if compared to the scheme with a cascade of 8 lines; therefore, the latter can be determined as an optimal solution. An electro-optical method was proposed for solving the radio engineering problem of stroboscopic registration and reconstruction of subnanosecond radio pulses, which represent the signature of the radio image of dynamic objects for active radio imaging systems.Conclusions. It was found that an electro-optical repeater with 8 delay lines is able to recover a complex pulse reflected from a target in 30 iterations with a correlation coefficient greater than 0.9 between the reference and reconstructed pulses at a signal-to-noise ratio of at least 9 dB.